Trends and Perspectives in Web-Based Science Learning Research: Evidence from 2015–2025 - Syifa Khairina Akhlida; Siswanto Siswanto; Ahmad Muhlisin (Universitas Pendidikan Mandalika, 2026)
This study aims to examine trends, challenges, and effectiveness in research on web-based science learning published between 2015 and 2025. A systematic literature review (SLR) method was employed. An initial pool of 150 articles was retrieved from international and national academic databases, including Web of Science, Scopus, and SINTA, using keywords related to web-based science education. Following relevance screening and the application of inclusion criteria, 104 articles were selected for in-depth analysis. The data were analyzed using thematic analysis with open coding to identify research trends, categorize technological innovations, and map challenges and opportunities associated with the implementation of web-based science learning. The findings reveal a substantial increase in research publications during the COVID-19 pandemic period, with Indonesia and Malaysia emerging as the primary contributors and physics being the most frequently studied subject area. Key challenges identified include limited digital infrastructure, low levels of digital literacy, underdeveloped instructional materials, and difficulties in conducting online assessments. In contrast, Learning Management Systems (LMS), virtual laboratories, and interactive digital media were found to be the most effective supporting technologies. These findings suggest that the success of web-based science learning depends on the integration of supportive policies, pedagogical innovation, appropriate technological tools, and international collaboration to develop an inclusive and adaptive digital science education ecosystem.